2016
DOI: 10.3389/fmars.2016.00134
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Iron Complexation for Fenton-Mediated Hydroxyl Radical Production at Circumneutral pH

Abstract: The reaction between Fe(II) and H 2 O 2 to yield hydroxyl radicals (HO • ), the Fenton reaction, is of interest due to its role in trace metal and natural organic matter biogeochemistry, its utility in water treatment and its role in oxidative cell degradation and associated human disease. There is significant dispute over whether HO • , the most reactive of the so-called reactive oxygen species (ROS), is formed in this reaction, particularly under circumneutral conditions relevant to natural systems. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 84 publications
4
65
0
Order By: Relevance
“…Therefore, they provide a powerful platform to study the membrane properties and interaction of reactive species with lipid bilayer [ 34 , 35 , 36 ]. Various methods have been developed for generating reactive species, such as Fenton reaction [ 37 , 38 ], photolysis [ 39 , 40 ] and cold physical plasma (CPP) [ 41 , 42 ]. CPP as ionized gas with temperature close to human body temperature can be produced by different sources such as plasma jets or dielectric barrier discharges [ 42 , 43 ], and beneficial effects have been shown in several medical applications, including wound healing [ 44 , 45 ], cancer treatment [ 46 , 47 , 48 , 49 ] and dental care [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they provide a powerful platform to study the membrane properties and interaction of reactive species with lipid bilayer [ 34 , 35 , 36 ]. Various methods have been developed for generating reactive species, such as Fenton reaction [ 37 , 38 ], photolysis [ 39 , 40 ] and cold physical plasma (CPP) [ 41 , 42 ]. CPP as ionized gas with temperature close to human body temperature can be produced by different sources such as plasma jets or dielectric barrier discharges [ 42 , 43 ], and beneficial effects have been shown in several medical applications, including wound healing [ 44 , 45 ], cancer treatment [ 46 , 47 , 48 , 49 ] and dental care [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…For analysis of Fe(II) oxidation kinetics, it was assumed that Fe(II) is mainly oxidised by O2 due to its presence at a much higher concentration than other potential oxidants such as reactive oxygen species. This is a reasonable assumption given that with the relatively low (at most 20 nmol (Miller et al 2009;Miller et al 2016). This means that micromolar concentrations of H2O2 are needed to outcompete O2 and affect the oxidation rate; therefore only the reaction between Fe(II) and O2…”
Section: Analysis Of Fe(ii) Oxidation Kineticsmentioning
confidence: 99%
“…Despite this, Miller et al [ 66 ] found that, in view of an ill-defined speciation status and oxidation mechanism, predictions of ● OH radical production from Fe(II)/Fe(III)-citrate complex(es) were poor, unlike results they obtained for these metal ions’ well-characterized 1:1 EDTA and diethylenetriamine-penta-acetate (DTPA) complexes; 1:1 iron(III)-citrate complexes are well known to be heterogeneous, including a range of oligomeric/polymeric adducts with co-complexing oxo/hydroxo ligands [ 67 ]. Indeed, for these EDTA-/DTPA-chelated Fe(II)/Fe(III) systems, they found that at circumneutral (soil) pH values (6.5-7.5), ● OH radical was the only species formed, and kinetic modelling suggested that ‘between-ligand’ differences found in the levels of its production were largely explicable by full considerations of all possible reactions between the redox-active Fe(II)-chelate/Fe(III)-chelate system and reactive oxygen species (ROS).…”
Section: Physicochemical Considerations For the Involvement Of Permentioning
confidence: 99%